PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWAKELAS VIII SMPN 4 PAINAN TAHUN PELAJARANAN 2013/2014 - Dwi Rusdi, Septian; Rahmi, Rahmi; sovia, Anny (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Research is based on a reality that the student ability in understanding the concept of mathematic is still low, the students are less active in learning process, student are hardly rise a question in learning process. The purpose of the research is to know how the learning process of mathematic by students and are they applying the learning type of the power of two to see if this method is better than other mathematic conventional type. The instrument of the research is an observation check list and final examination as the indicator of understandingÂ the concept. An essay examination is used with reliable test score r11 = 0,91 hypotesis used is one side test-t with a MINITAB application. Based on the datas analysis result, p-value = 0,012 smaller than Â so the hypotesis result is accepted. The conclusion of the research is the learning strategy applied by the method of the power of two is better than the conventional method used by the students and the students activities are increasing in every session of grade VIII SMPN 4 Painan.